Macroeconomic Fluctuations in Home Countries and Immigrants’ Well-Being: New Evidence from Down Under - Nguyen, Ha; Duncan, Alan (My University, 2020)
This article exploits plausibly exogenous changes in macroeconomic conditions across home countries over time and panel individual data to examine the causal impact of home countries’ macroeconomic conditions on immigrants’ well-being in Australia. We present new and robust evidence that immigrants in Australia feel happier when their home countries’ macroeconomic conditions improve, as measured by a higher gross domestic product (GDP) per capita or lower price levels. Controlling for immigrants’ observable and unobservable characteristics, we also find that the positive GDP impact is statistically significant and economically large in size. Furthermore, the GDP and price impact erodes as immigrants age or stay in the host country beyond a certain period of time. Our findings suggest that immigrants in Australia have emotional or altruistic connections to their home countries and appear encouraging for home countries increasingly attempting to convince their diasporas to contribute more to the development of their homelands.
International Migration Review
Keywords: Culture and language; Families and relationships; Health and wellbeing; Identity; Income, wealth and finances; International comparison; Labour market; Lifestyle; Migration and settlement; Social engagement